2018
DOI: 10.1016/j.jfda.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Wedelia chinensis leaf-assisted silver nanoparticles for antioxidant, antibacterial and in vitro cytotoxic applications

Abstract: Green synthetic route of silver nanoparticles (AgNPs) has already been proved to be an advantageous over other physico-chemical approaches due to its simplicity, cost effectiveness, ecofriendly and nontoxicity. In this finding, aqueous Wedelia chinensis leaf extract (WLE) mediated synthesis of AgNPs was approached. Surface plasmon resonance (SPR) band at 408 nm preliminary indicated the formation of AgNPs, while TEM and XRD characterization confirmed the formation of spherically shaped and crystalline AgNPs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Ag peaks are detected at 365–376 eV ( Figure 5 b,f). As a spin-orbital splitting, the Ag3d peak is shown as a doublet with two states: 367.5 eV Ag3d 5/2 and 373.5 eV Ag3d 3/2 with splitting energy of 6 eV, confirming the state in Ag 0 [ 52 , 53 ]. Figure 5 c describes the deconvolution of C1s spectra from AgNDs with four signals at 284.28, 285.5, 286.39, and 287.66 eV with respect to the C=C, C–O, C–N, and C=O relationships [ 54 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 87%
“…Ag peaks are detected at 365–376 eV ( Figure 5 b,f). As a spin-orbital splitting, the Ag3d peak is shown as a doublet with two states: 367.5 eV Ag3d 5/2 and 373.5 eV Ag3d 3/2 with splitting energy of 6 eV, confirming the state in Ag 0 [ 52 , 53 ]. Figure 5 c describes the deconvolution of C1s spectra from AgNDs with four signals at 284.28, 285.5, 286.39, and 287.66 eV with respect to the C=C, C–O, C–N, and C=O relationships [ 54 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 87%
“…The results were in agreement with previous studies, in which the synergic effect of AgNPs and herbal extracts against various pathogenic bacteria was proved. 69–73 In term of particle size, the small size of AgNPs (4–5 nm) as well as the small size of Allium@AgNPs (13.5 nm) might contribute to high antibacterial property of the nanosystem. 74–76 Patra and Baek et al suggested that the AgNPs could strongly bind to the bacterial cell wall, then disrupt its structure.…”
Section: Resultsmentioning
confidence: 99%
“…Nestlé’s low-fat ice cream uses nanoemulsions to achieve a low-fat content ( Sampathkumar, Tan & Say, 2020 ). These nanomaterials, as shown in several studies, enhance food packaging effectiveness, shelf life, and nutritional value without altering the flavor and physical properties of the food ( Bajpai et al, 2018 ; Paul Das et al, 2018 ). NDS has also been successfully used as processing aids, quality enhancers, antimicrobial agents, as well as in the creation of sensors for evaluating quality, safety and enhancement of the product’s physicochemical characteristics, nutrition and bioavailability ( Patra, Shin & Paramithiotis, 2018 ).…”
Section: Applications Of Nano-delivery Systems In Food Product Develo...mentioning
confidence: 96%